KLASIFIKASI TUTUPAN LAHAN PADA HUTAN LINDUNG GUNUNG SIRIMAU KOTA AMBON - Marleen A. Tuakora; Gun. Mardiatmoko; Henderina Lelloltery (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
Protected forest is a forest area that has the main function of protecting life support systems, to arrange water management, preventing flooding, erosion and sea water intrusion. The information of land cover is very important to determine the distribution of spatial use patterns on environmental conditions and regional spatial planning. This research aims to know the classification of land cover in Gunung Sirimau Protected Forest area in 2000, 2009 and 2019, and to identify the level of accuracy of the classification. This research used remote sensing and GIS methods to identify land cover classes using land cover maps released by the Ministry of Environment and Forestry in 2000, 2009 and 2019. The results of this research are classification of land cover in 2000 consist of primary dryland forest, secondary dryland forest, shrubs, and mixed dryland farming. Land cover in 2009 has an additional classification that is residential land, and in 2019 also has an additional classification that is open land. Overall accuracy value with ground checking obtained accuracy level 86,67% from 15 sample points.